Faktor Komorbid Yang Berpengaruh Terhadap Luaran Penyakit Covid 19 Di Intensive Care Unit RSUP Dr Kariadi Semarang - Harahap, Sofyan; Mulyono, Harry; Soesilowati, Danu (RSUP Dr. Kariadi, 2021)
BACKGROUND : Sars-Cov2 has become a pandemic and caused health problems. Several factors that worsen the condition of Covid-19 include age, previous comorbid diseases, secondary infections, and increased inflammatory indicators. There are many studies on the factors that influence the outcome of Covid-19, but the results are inconsistent. Thus, specific research in certain areas is needed so that it can be used in local management. OBJECTIVE: This study aims to determine the factors that influence the outcome of Covid-19 in the intensive care unit of the Dr. Kariadi Hospital METHOD : This study analyzed covid 19 patients in the ICU of Dr Kariadi Hospital for the period March-September 2020 with a retrospective method and purposive sampling. The hypothesis test used is adjusted to the measurement scale of each variable. The initial analysis was univariate using chi-square, fisher, t-test, and mann-whitney. RESULT : From this study, it was found that the factors that influence the covid-19 outcome in a bivariate include a history of heart disease (p = 0.037), temperature (p = 0.012), respiratory rate (p = 0.030), oxygen saturation (p = 0.021), platelets ( p = 0.015), ureum (p = 0.034), PO2 (p = 0.002), oxygen fraction (FiO2) (p = 0.034), AaDO2 (p = 0.004), and PFR (p = 0.001). CONCLUSION : History of heart disease, temperature, respiratory rate, oxygen saturation, platelets, urea, PO2, required oxygen fraction (FiO2), AaDO2, and PFR were predictors of Covid-19 mortality which were both theoretically and statistically significant.,independent or simultaneously